Impact of Patient Language on Emergency Medical Service Use and Prenotification for Acute Ischemic Stroke. (January 2019) - Rostanski, Sara K.; Kummer, Benjamin R.; Miller, Eliza C.; Marshall, Randolph S.; Williams, Olajide; Willey, Joshua Z.
Background and Purpose: Use of emergency medical services (EMS) is associated with decreased door-to-needle time in acute ischemic stroke (AIS). Whether patient language affects EMS utilization and prenotification in AIS has been understudied. We sought to characterize EMS use and prenotification by patient language among intravenous tissue plasminogen activator (IV-tPA) tissue plasminogen (IV-tPA) treated patients at a single center with a large Spanish-speaking patient population. Methods: We performed a retrospective analysis of all patients who received IV-tPA in our emergency department between July 2011 and June 2016. Baseline characteristics, EMS use, and prenotification were compared between English- and Spanish-speaking patients. Logistic regression was used to measure the association between patient language and EMS use. Results: Of 391 patients who received IV-tPA, 208 (53%) primarily spoke English and 174 (45%) primarily spoke Spanish. Demographic and clinical factors including National Institutes of Health Stroke Scale (NIHSS) did not differ between language groups. Emergency medical services use was higher among Spanish-speaking patients (82% vs 70%; P < .01). Prenotification did not differ by language (61% vs 63%; P = .8). In a multivariable model adjusted for age, sex, and NIHSS, Spanish speakers remained more likely to use EMS (odds ratio: 1.8, 95% confidence interval: 1.1-3.0). Conclusion: Emergency medical services usage was higher in Spanish speakers compared to English speakers among AIS patients treated with IV-tPA; however, prenotification rates did not differ. Future studies should evaluate differences in EMS utilization according to primary language and ethnicity.